SHAXS TASHABBUSKORLIGINING O‘RGANILGANLIK DARAJASI - Jurayeva, H.A. (SCIENCE and SOCIETY, 2024)
This article shows the degree of awareness of the initiative of the individual. There is obtained different results while comparing the initiative with various other personality traits.